The moderating effect of culture on the relationship between women directors and CSR disclosure in Malaysia - Intan Maiza Abd Rahman,; Ku Nor Izah Ku Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examines the moderating effect of culture on the relationship between women directors and CSR disclosure. The reason for examining this issue is twofold. First, the effort and focus to improve the representation of women on corporate boards in Malaysia is continually being discussed since 2011. Thus, having women on corporate boards may affect company’s CSR disclosure differently if compared to when boards are dominated by men. Second, having multi-ethnic boards may also influence the decision-making process in that different ethnic groups would react differently in the decision making process related to CSR disclosures, for example it is assumed that boards dominated by Malays would react differently if compared to boards dominated by other ethnic groups. Data for this study is collected from company’s annual report for the year 2013. Three hundred (300) companies were used as the sample of this study. Two theories were applied in this study: transformational leadership theory and cultural theory. Using a hierarchical regression analysis, this study finds that culture influences CSR disclosure, and moderates the effects of women directors on companies’ CSR disclosure. The moderating effect could be interpreted that women directors positively influence companies’ CSR disclosure and are able to exercise their transformational leadership style when boards are dominated by Malay directors. The findings of this study support the efforts taken by the government at increasing the Malay (or Bumiputra) and women participation at decision-making level.